Faktor-Faktor yang Mempengaruhi Kepuasan dan Kepercayaan untuk Mencapai Loyalitas Pasien Rawat Inap pada Rumah Sakit Swasta di Kota Banjarmasin - Djohan, Agustinus Johanes (Universitas Brawijaya, Indonesia, 2015)
This research aims to learn, analyze and prove the influence of 1) hospital reputationto patients’satisfaction at private hospital at Banjarmasin, 2) hospital reputation topatients’trust at private hospital at Banjarmasin, 3) reliability of doctors to patients’satisfactionat private hospital at Banjarmasin, 4) reliability of doctors to patients’trust atprivate hospital in Banjarmasin city, 5) reliability of nurses to patients’satisfaction at privatehospital at Banjarmasin, 6) ) reliability of nurses to patients’trust at private hospital atBanjarmasin city, 7) operational benevolence to patients’satisfaction at private hospital atBanjarmasin, 8) operational benevolence to patients’trust at private hospital in Banjarmasincity, 9) patients’satisfaction to patients’trust at private hospital at Banjarmasin, 10) satisfactionto patients’loyalty at private hospital at Banjarmasin, 11) trust to patients’loyalty atprivate hospital at Banjarmasin. Populations of this research are patients from three privatehospitals at Banjarmasin. There are 250 respondents by using structural equation modelling(SEM). The research reveals that; 1) hospital’s reputation influences significantly positiveto patients’satisfaction at private hospitals at Banjarmasin, 2) hospital’s reputationinfluences significantly positive to patients’trust at private hospitals at Banjarmasin, 3)doctors’reliability influences significantly positive to patients’satisfaction at private hospitalsat Banjarmasin, 4) doctors’reliability influences significantly positive to patients’trustat private hospitals at Banjarmasin, 5) nurses’reliability influences significantly positive topatients’satisfaction at private hospitals at Banjarmasin, 6) nurses’reliability influencessignificantly positive to patients’trust at private hospitals at Banjarmasin, 7) operationalbenevolence influences significantly positive to patients’satisfaction at private hospitals atBanjarmasin, 8) operational benevolence influences significantly positive to patients’trustat private hospitals at Banjarmasin, 10) patients’satisfaction influences significantly positiveto patients’loyalty to be hospitalized at private hospitals at Banjarmasin, 11) patients’trust influences significantly positive to patients’loyalty to be hospitalized at private hospitalsat Banjarmasin.